GEOCHEMICAL BACKGROUND - WHAT A COMPLEX MEANING HAS SUCH A SIMPLE EXPRESSION! - Licht, Otavio Boni (Geochimica Brasiliensis, 2020)
The term background was introduced in geochemistry applied to the prospecting of mineral deposits to designate a value, below which the samples would represent normal contents and above which they would be deviations from normality and could represent anomalies related to mineral deposits. In the 1980’s, when the techniques applied in mineral exploration were absorbed by the nascent environmental sciences, the term background was also incorporated with a very similar meaning. However, since its first application, this term has been adopted arbitrarily, without considering the enormous diversity of underlying variables that can substantially alter its numerical meaning. In this article, the large number of components that make up this "complex system" known as geochemical background will be presented and discussed, and which cover virtually all concepts of geochemical exploration whether applied in geological-mining or environmental actions, such as: the type of sample collected, the sample preparation procedures, the fraction to be analyzed, the analytical technique used, the criterion for choosing the value, the sample density, the spatial variability and the variations over time.